Tanggung Jawab Notaris terhadap Ketidaksesuaian Akta Salinan dengan Minuta Akta - Halim, Yoefanca; Sudewo, Fricky; Fidelia, Tyas (Jurnal Ilmiah Penegakan Hukum, 2019)
Notary as a general official has authorization in making an authentic deed and have other powers as referred to in this law or under other laws, as described in the Department of Law Notary. In carrying out his position, a notary is obliged to act as a trustee, honest, equitable, independent, immutated, and keep the interests of the parties and to make the deed Minuta. In addition, a notary is obliged to issue the Grosse deed, copy of the deed, or Deed citation based on Minuta deed, such matters are governed by Law No.2 of 2014 as has been amended by Law No. 30 of 2004 on the Department of notary. It means that a notary is supposed to carry out obligations. But in fact, the notary can still be found that does not carry out obligations as stipulated in the notary law. By looking at this raises an issue about, "What is Notary's responsibility for the inconsistency of the Copy act with the Minuta deed?". In general, the responsibilities of notary public can be examined in the public, criminal, notary LAW, and responsibility for performing the duties of the department under the notary Code of Ethics. Civil liability regarding material truth in the deed made and can be categorized as making false documents in criminal terms. While the responsibilities according to the LAW and the Code of Ethics Department notary, notary may be subject to sanctions in the form of oral warning, letters, temporary stops, and stops with respect or disrespect.